Adsorption of Glucose within M(IV)‐Incorporated Zeolites: Insights from Periodic Density Functional Theory Calculations. Issue 21 (21st December 2016) - Yang, Gang; Zhu, Chang; Zhou, Lijun
Abstract: Albeit the isomerization mechanism of glucose to fructose catalyzed by M(IV)‐incorporated zeolites is widely studied, scant attention has been given to the adsorption of related sugars that is critical to catalysis. Here p‐DFT calculations are conducted to have a comprehensive understanding within this context, considering the effects of adsorption modes, identity of framework‐M(IV) ions, pore topology and conformational states of glucose. Monodentate rather than bidentate adsorption structures of glucose are the most energetically favorable within all investigated zeolites except Sn‐CHA. Adsorption performances of different M(IV)‐incorporated BEA zeolites decline as Zr > Sn > Ti > Ge, where Ti‐ and Ge‐BEA, especially the latter, is obviously inferior for sugar adsorption and catalysis. Pore topology of zeolites plays an even more pronounced effect during glucose adsorption. Non‐covalent interactions contribute significantly to the adsorption processes. Dispersion effects of different framework‐M(IV) ions, although close to each other, show a clear opposite trend as adsorption energies. FER rather than other zeolites shows surprisingly high dispersion effects (e. g.; −218 kJ/mol for Sn‐FER vs. −123 kJ/mol for Sn‐BEA). It also shows that dispersion effects for the various conformational states of glucose are closely related with structural flexibilities. Abstract : Cellulosic biomass represents a promising energy source of the future while its direct conversion to downstream products remains challenging. M(IV)‐incorporated zeolites show unprecedented catalytic performances for glucose isomerization to fructose, one of the key reactions for cellulosic transformation. Adsorption of glucose is the essential first step of the isomerization reaction and is presently investigated by periodic density functional theory calculations, considering effects of adsorption modes, M(IV)‐incorporated ions, pore topologies and non‐covalent interactions.